A proposal to synonymize Loffienema with Haematozoon, Quercorhabditis with Diploscapteroides, and Stegorhabditis with Stomachorhabditis (Nematoda, Rhabditida, Rhabditomorpha), including keys to species identification - Abolafia, Joaquín (Zootaxa, 2023)
The morphology of three genera of the family Rhabditidae, Loffienema, Quercorhabditis and Stegorhabditis, described recently from Jammu and Kashmir (India), is analyzed in detail. After the revision of their morphology, these genera are proposed to be synonymized with other three known genera: Loffienema with Haematozoon, Quercorhabditis with Diploscapteroides, and Stegorhabditis with Stomachorhabditis. In addition, the taxonomic status of the genus Distorhabditis is discussed. Dichotomous keys for the identification of species of the genera Haematozoon, Diploscapteroides and Stomachorhabditis are included.